Libman-Sacks endocarditis in patients with systemic lupus erythematosus with secondary antiphospholipid syndrome - Yousef Mohammadi Kebar; Leili Avesta; Afshin Habibzadeh; Mehdi Hemmati (Babol University of Medical Sciences, 2019)
Background: Libman-Sacks endocarditis (LSE) is characterized by sterile lesions that commonly affect the aortic and mitral heart valves. Antiphospholipid syndrome (APS) and systemic lupus erythematosus (SLE) have been associated with LSE. Cardiac manifestations including LSE could be interrelated with other manifestations and early diagnosis could help in preventing further complications. Case presentation: Here, we report three cases of LSE in SLE patients with secondary APS. All patients presented with neurological manifestations and LSE was diagnosed by Transesophageal echocardiography (TEE). All three patients were treated for the underlying disease and also received anticoagulant therapy. Conclusion: In all patients with SLE and secondary APS, LSE should be considered if a patient manifests any evidence of neurologic involvement.